Dyspepsia as a Trigger for Sleep Disorders: A Case Study of Gut–Brain Axis Interaction - Friska Febrian Damayanti; Hafid Algristian; Marintik Ilahi (Indonesian Scientific Publication, 2026)
Functional dyspepsia is an upper gastrointestinal complaint without organic abnormalities that may interact with sleep through gut–brain axis mechanisms. We report the case of a 49-year-old woman with persistent insomnia occurring concurrently with epigastric pain for approximately one year. The patient relied on hypnotic medication and experienced early-morning awakenings. Psychiatric, somatic, and psychosocial evaluations indicated that the sleep disturbance was related to dyspeptic complaints. Management included psychoeducation, supportive psychotherapy, and Cognitive Behavioral Therapy for Insomnia (CBT-I), along with dyspepsia therapy (sucralfate and omeprazole) and a spiritual approach according to the patient’s preferences. Following integrated therapy, sleep patterns improved and the Insomnia Severity Index score decreased in parallel with the resolution of dyspepsia symptoms. This case demonstrates that dyspepsia can trigger sleep disturbances through gut–brain axis mechanisms and highlights the importance of a multidisciplinary approach in managing insomnia with gastrointestinal comorbidity. The report also emphasizes the clinical relevance of addressing biopsychosocial factors and incorporating culturally sensitive, patient-centered care to enhance therapeutic outcomes and prevent symptom recurrence.